Adaptive potential of winter wheat varieties under contrasting conditions of mineral nutrition in the middle Don - K. N. Biryukov; A. I. Grabovets; M. A. Fomenko; O. V. Biryukova; I. V. Lyashkov (Зерновое хозяйство России, 2023)
The current study was carried out to research the adaptive potential of winter wheat varieties depending on the level of mineral nutrition in the soil and climatic conditions of the north of the Rostov region in 2012–2018. The objects of the study were 10 winter wheat varieties bred by FGBSI FRARC. Between 2012 and 2014 there were studied 6 wheat varieties (the first group), in 2015–2018 there were studied 4 ones (second group). The soil of the experimental plot was represented by southern medium-thick calcareous chernozem. The experimental scheme included 12 backgrounds of mineral nutrition. Crops were laid weedfree fallow, the seeding rate was 4 million germinating seeds per 1 ha for each agricultural variant. Agro-climatic conditions in the experimental years were contrasting. As a result of the study, there was found that in the first group of varieties, the factor ‘variety’ had the greatest influence on productivity formation (64.4 %), in the second group it was the factor ‘agrobackground’ (71.0 %). Productive possibilities (according to the coefficient of adaptability) of the varieties ‘Donskaya Lira’, ‘Donna’, ‘Zolushka’, ‘Boyarynya’ and ‘Donera’ were high, they amounted to 101–108 %. In contrasting conditions of mineral nutrition, the above listed varieties had an optimal ratio between the needs of the genotype and the level of the agricultural background. The varieties ‘Boyarynya’ and ‘Donna’ in their groups formed the maximum yield with 6.71 t/ha of for ‘Boyarynya’ and 6.42 t/ha for ‘Donna’. In the course of the current work, there was found that the varieties ‘Missiya’ and ‘Tarasovskaya 70’ had high adaptability to a limited amount of fertilizers. The optimal combination of parameters of ecological adaptability and stability were found for the varieties ‘Donskaya Lira’, ‘Boyarynya’, ‘Vestnitsa’, ‘Donstar’, ‘Donera’. They had a wide range of adaptive capabilities, therefore, under production conditions, they could produce a stable grain yield with various variations in the level of mineral nutrition.